The Security Council in Settlement of International Disputes as a World Adjudicator: Legal and Political Challenges - Fatema , Urooj; Hussain , Syed Imran; ., Manaswi; ., Yashaswi; Ranjan , Navodit (International Journal of Membrane Science and Technology, 2023)
Security Council considered an indispensable body acting as the World’s adjudicator is responsible for resolving disputes under the various Member States. Such obligations and duties come with their own sets of Pros and Cons. Better procedure is not a replacement for UN member states' desire to uphold their duties under the Charter in good faith, although routinizing procedure frequently makes it easier for nations to uphold their obligations. It is always far easier to follow a standard method than to request a deviation from it. The Council acting continually, as originally envisaged by Article 28(1) of the Charter, as opposed to only during times of emergency, would provide the most benefit in the long run. Its members would grow more cooperative and knowledgeable about the interconnection of the various elements of global peace and maintenance of peace would become a primary task for them. The article thus addresses the persistent questions surrounding the Security Council's role in resolving international conflicts, which present their own legal and political difficulties ranging from the character of resolutions to the Council's own act of initiating such problems.